DEVELOPMENT OF A DEVICE PROJECT THAT DETERMINES THE AMOUNT OF ELEMENTS THAT ENSURE SOIL FERTILITY (POTASSIUM, CALCIUM, NITROGEN) - Kamolaxon , Haydarova; Abbosjon, To’ychiboyev; Nurmatov, Sardor (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
Determining soil fertility and effectively managing it is one of the urgent issues in agriculture. Modern technologies play a crucial role in automatically analyzing soil composition and optimizing fertility to increase crop yields. This article highlights the importance of monitoring and optimizing soil fertility through automated systems. The main elements of the soil are measured using an NPC sensor, and the data is sent to the microchip. The analyzed data from the microchip is displayed on an OLED screen. Additionally, the article provides information and guidelines on designing the schematic of this project, connecting sensors and actuators to the microcontroller, and writing the program code.